Implications of E-Banking on Household Financial Management - Nuhasanah, Nuhasanah; Nugraha, Hendri Adi (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2023)
Financial management is carried out for small businesses as well as for major corporations, including digital financial services for consumers. As a result, it has an impact on how consumers use financial technology. Understanding behavioral changes in home finance management is the goal of this study. This study employed a qualitative methodology. Primary research data in the form of a questionnaire was used. Samples were collected from Pekalongan City homes. The study's findings indicated that because m-banking makes it so simple to conduct transactions, housewives who continue to keep track of their household's financial statements prefer to use banks when making deposits.